The age of Keynes - Lekachman, Robert (London : Allen Lane the Penguin P., 1967)
This book is also the biography of a mind, an effort to trace the events and the influences which converted the inventive pupils of conventional economics into the most influential heretic of his age.
Includes bibliographies.
ijb, 14/01/2019
Loans
Keywords: Keynes, John Maynard; Keynesian economics